Position statement on ethics, equipoise and research on charged particle radiation therapy. Issue 8 (17th September 2013) - Sheehan, Mark; Timlin, Claire; Peach, Ken; Binik, Ariella; Puthenparampil, Wilson; Lodge, Mark; Kehoe, Sean; Brada, Michael; Burnet, Neil; Clarke, Steve; Crellin, Adrian; Dunn, Michael; et al.
Abstract : The use of charged-particle radiation therapy (CPRT) is an increasingly important development in the treatment of cancer. One of the most pressing controversies about the use of this technology is whether randomised controlled trials are required before this form of treatment can be considered to be the treatment of choice for a wide range of indications. Equipoise is the key ethical concept in determining which research studies are justified. However, there is a good deal of disagreement about how this concept is best understood and applied in the specific case of CPRT. This report is a position statement on these controversies that arises out of a workshop held at Wolfson College, Oxford in August 2011. The workshop brought together international leaders in the relevant fields (radiation oncology, medical physics, radiobiology, research ethics and methodology), including proponents on both sides of the debate, in order to make significant progress on the ethical issues associated with CPRT research. This position statement provides an ethical platform for future research and should enable further work to be done in developing international coordinated programmes of research.